Partnership fundamentals: understanding organisational incentives - Stott, Leda (Revista Española de Desarrollo y Cooperación, 2023)
This article argues that the effective performance of multi-actor partnerships in the UN Sustainable Development agenda for 2030 rests upon deeper understanding of different organisational incentives for working in partnership. It explores the rationale for assessment of organisational incentives for partnering and provides practical pointers on how this analysis might be conducted. An early internal inquiry into whether or not to partner is recommended with wider discussion among potential partners as a desirable follow-up to this. The premise is that greater clarity around diverse incentives for partnering, and the issues and challenges that partners may face by working in these relationships, will enhance mutual understanding and support the improved effectiveness of collaborative engagement.
Keywords: Multi-actor partnerships; Collaboration; Organistaional incentives